Shorebird ecology, conservation, and management - Colwell, Mark A. (University of California Press, 2010)
Shorebirds are model organisms for illustrating the principles of ecology and excellent subjects for research. Their mating systems are as diverse as any avian group, their migrations push the limits of endurance, and their foraging is easily studied in the open habitats of estuaries and freshwater wetlands. This comprehensive text explores the ecology, conservation, and management of these fascinating birds. Beginning chapters examine phylogenetic relationships between shorebirds and other birds, and cover shorebird morphology, anatomy, and physiology. A section on breeding biology looks in d.